Front and Back Matter for Volume 2 Issue 6, November 2025 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2025)
Volume 2, Issue 6, November 2025 This issue consists of 5 articles contributed by 20 authors affiliated with 9 affiliations from three countries including Indonesia (Universitas Jambi, Universitas Hindu Indonesia, Universitas Jember, Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil Padang, Politeknik Perkapalan Negeri Surabaya, Poltekkes Kemenkes Pontianak), Somalia (East Africa University), Ethiopia (Jigjiga University, Haramaya University)